2002
DOI: 10.1128/jvi.76.13.6586-6595.2002
|View full text |Cite
|
Sign up to set email alerts
|

Previously Infected and Recovered Chimpanzees Exhibit Rapid Responses That Control Hepatitis C Virus Replication upon Rechallenge

Abstract: Responses in three chimpanzees were compared following challenge with a clonal hepatitis C virus (HCV) contained in plasma from an animal that had received infectious RNA transcripts. Two of the chimpanzees (Ch1552 and ChX0186) had recovered from a previous infection with HCV, while the third (Ch1605) was a naïve animal. All animals were challenged by reverse titration with decreasing dilutions of plasma and became serum RNA positive following challenge. Ch1605 displayed a typical disease profile for a chimpan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
132
4
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(154 citation statements)
references
References 33 publications
14
132
4
4
Order By: Relevance
“…During primary HCV infection of chimpanzees, virus-specific antibody responses are detectable 8 to 12 weeks after infection and HCV-specific T-cell responses appear with identical delays. 25,[38][39][40][41] This long interval of time between infection and induction of the adaptive immunity to HBV and HCV seems to contrast with the reported kinetics of virus-specific T-cell responses to other virus infections. Although comparison of different studies must be interpreted with caution because of possible sensitivity variations in the assays, it is intriguing that although T-cell responses to simian immunodeficiency virus, human immunodeficiency virus, and cytomegalovirus already can be detectable 2 weeks after infection, 42,43 Fig.…”
Section: Profiles Of Adaptive Immune Responses Early After Hbv and Hcmentioning
confidence: 99%
See 2 more Smart Citations
“…During primary HCV infection of chimpanzees, virus-specific antibody responses are detectable 8 to 12 weeks after infection and HCV-specific T-cell responses appear with identical delays. 25,[38][39][40][41] This long interval of time between infection and induction of the adaptive immunity to HBV and HCV seems to contrast with the reported kinetics of virus-specific T-cell responses to other virus infections. Although comparison of different studies must be interpreted with caution because of possible sensitivity variations in the assays, it is intriguing that although T-cell responses to simian immunodeficiency virus, human immunodeficiency virus, and cytomegalovirus already can be detectable 2 weeks after infection, 42,43 Fig.…”
Section: Profiles Of Adaptive Immune Responses Early After Hbv and Hcmentioning
confidence: 99%
“…It is interesting to note that HCVspecific cellular immune responses are detectable earlier after rechallenge (2 weeks) than after primary infection (8-10 weeks). 39,41,128,131 This acceleration of the adaptive immune response, although insufficient to prevent infection, can influence positively the course of the HCVinduced liver disease in vaccinated animals, which usually develop low viremia and mild hepatitis. These findings in HCV rechallenge experiments and in HCV-vaccinated animals reinforce the hypothesis that the long interval of time between infection and activation of the HCVspecific adaptive immune response represents a major factor that influences the rate of chronicity and the profile of the disease.…”
Section: Final Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been shown that there is an inverse correlation between the frequency of HCV-specific cytotoxic T lymphocytes and virus load (Nelson et al, 1997). More recently, it was shown that the control of HCV in chimpanzees was associated with a Th1-type cellular immune response (Major et al, 2002). Therefore, accumulated evidence suggests an important role for HCV-specific T-cell responses in controlling HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in reinfected chimpanzees that previously cleared the infection have revealed the existence of a protective immunity, which may, however, not be able to consistently prevent reinfection (Bukh et al, 2008;Major et al, 2002). The protection seems to be T-cell-mediated (reviewed by Bowen & Walker, 2005).…”
Section: Chimpanzee Model: Adaptive Immune Responsesmentioning
confidence: 99%